The Influence of Safety and Health Representatives in the Western Australian Mining Industries - Chakraborti, Shibani (Curtin University, 2018)
The aim of this research was to identify what influence and support Safety and Health Representatives had in the Western Australian mining industries to facilitate the achievement of a high standard of workplace safety. A hermeneutic phenomenological approach was used to conduct this qualitative research. Results identified that management support was the most important factor for the work of Safety and Health Representatives to be effective. Findings will be used to improve OSH legislation.